3D Porous Fused Aromatic Networks for High Performance Gas and Iodine Uptakes (Adv. Mater. Interfaces 22/2021). Issue 22 (23rd November 2021) - Ahmad, Ishfaq; Noh, Hyuk‐Jun; Yu, Soo‐Young; Jeon, Jong‐Pil; Sun, Qikun; Mahmood, Javeed; Baek, Jong‐Beom
Abstract : 3D Porous Fused Aromatic Networks In article number 2101373, Ishfaq Ahmad, Javeed Mahmood, Jong‐Beom Baek, and co‐workers report the design and synthesis of two new 3D porous organic networks (PONs) with fused aromatic structures. The PONs' structures are constructed by the double condensation reaction between tetrapodal octaamine and pyrenetetraketone (PTK) or hexaketocyclohexane (HKH) to produce PTK‐PON (P‐PON) or HKH‐PON (H‐PON), respectively. The synthesized PONs exhibit high adsorption performance for small molecules such as CO2, H2, CH4, and I2 . The image represents the adsorption of gases on the 3D PONs.